Predicting inpatient aggression by self‐reported impulsivity in forensic psychiatric patients. (17th April 2015) - Bousardt, Annelea M. C.; Hoogendoorn, Adriaan W.; Noorthoorn, Eric O.; Hummelen, Jacobus W.; Nijman, Henk L. I.
Abstract: Background: Empirical knowledge of 'predictors' of physical inpatient aggression may provide staff with tools to prevent aggression or minimise its consequences. Aim: To test the value of a self‐reported measure of impulsivity for predicting inpatient aggression. Methods: Self‐report measures of different domains of impulsivity were obtained using the Urgency, Premeditation, Perseverance, Sensation seeking, Positive urgency (UPPS‐P) impulsive behaviour scale with all 74 forensic psychiatric inpatients in one low‐security forensic hospital. Aggressive incidents were measured using the Social Dysfunction and Aggression Scale (SDAS). The relationship between UPPS‐P subscales and the number of weeks in which violent behaviour was observed was investigated by Poisson regression. Results: The impulsivity domain labelled 'negative urgency' (NU), in combination with having a personality disorder, predicted the number of weeks in which physical aggression was observed by psychiatric nurses. NU also predicted physical aggression within the first 12 weeks of admission. Conclusions and implications for practice: The results indicate that NU, which represents a patient's inability to cope with rejection, disappointments or other undesired feelings, is associated with a higher likelihood of becoming violent while an inpatient. This specific coping deficit should perhaps be targeted more intensively in therapy. Self‐reported NU may also serve as a useful adjunct to other risk assessment tools and as an indicator of change in violence risk. Copyright © 2015 John Wiley & Sons, Ltd.